Pengaruh Regulasi PPN dan PPnBM serta Pendapatan Terhadap Minat Beli Kendaraan Bermotor Roda Empat (Mobil) di Indonesia - Dian Anggraeni; Hasna Mudiarti (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2022)
This study aims to analyze the influence of the Minister of Finance Regulation Number 77/PMK.010/21 and income on interest in purchasing car in Indonesia. This research is a quantitative study with the Indonesian population and the sampling is determined by random sampling method by distributing questionnaires randomly in several areas. The data was analyzed using the PLS analytic method with SmartPLS software, which included evaluation of the measurement, evaluation of the structural model, and hypothesis testing. The results revealed that regulation and income had a positive and significant effect on interest in car. The R-Squares value was obtained at 61.8%, indicating that the interest in purchasing four-wheeled motorized vehicles is influenced by regulation and income, with the rest explained by other variables not included in this study.